Characterization of the structural rheological properties of wood flour–polyethylene composites with ultrahigh filling on the basis of uniaxial cyclic compression method. (February 2022) - Fu, Haitao; Dun, Mengyuan; Wang, Haigang; Zou, Chuwen; Wang, Limin; Zhou, Zhifang; Wang, Weihong; Xie, Yanjun; Wang, Qingwen
Abstract: Understanding structural changes in wood–plastic composites with ultrahigh filling (wood flour content >70 wt%, UF–WPCs) during melt flow is the key to improving product quality and production efficiency. However, the rheological behavior of UF–WPCs is often difficult to characterize because of its extremely poor fluidity and strong solid-like attribute. In this study, a specific methodology based on uniaxial compression tests was developed to characterize the structural rheological properties of wood flour–polyethylene composites with ultrahigh filling (UF–WFPEs) under different conditions. During cyclic compression tests, the parameters, such as the elastic modulus, yield stress, strain energy density, dissipation energy index, adhesive strength, and adhesive energy, were calculated to identify the structural rheological properties of the UF–WFPE melt. The reliability and sensitivity of this method were verified under different operating conditions. This study provides a feasible method for the rheological analysis of UF–WPCs.